Examining Energy Futures Market Efficiency Under Multiple Regime Shifts - Buberkoku, Onder (International Journal of Energy Economics and Policy, 2017)
This study examines the West Texas Intermediate crude oil (WTI), Europe Brent crude oil (Brent), heating oil no. 2, and Henry Hub natural gas futures markets’ efficiency following Fama’s (1970) weak-form efficiency hypothesis, using spot and futures prices at 1, 2, 3, and 4 months maturity based on the tests with unknown multiple regime shifts. The results show that it is important to consider the multiple regime shifts when determining whether energy futures markets are efficient. We find that WTI and Brent futures markets are not efficient, whereas natural gas and heating oil futures markets are efficient. Additionally, the findings also shed light on discussions about the stationary properties of energy commodities and whether spot and futures prices are cointegrated. In particular, this study presents new evidence based on the unit root and cointegration tests with multiple structural breaks. Keywords: Energy commodity, Futures market efficiency, Multiple structural breaks JEL Classifications: G14, G15, Q40